Dynamics, Analysis and Institutional Framework of Birth Rate in Bulgaria - Koleva–Stefanova, Desislava (Research Papers, 2019)
This article analyses the demographic situation in Bulgaria and identifies more significant problems related to fertility. The purpose of the study is based on three indicators characterizing the birth rate in Bulgaria, the 28 areas, to be grouped into four homogeneous сlusters and to define indicators that contribute most to the formation of the groups. Based on the research are formulated, some recommendations related to the stimulation of fertility in Bulgaria.
Keywords: Birth rate; Fertile age; Birth policy; Natural growth; Active policy